Allelic barley MLA immune receptors recognize sequence-unrelated avirulence effectors of the powdery mildew pathogen - Lu, X.; Kracher, B.; Saur, I.; Bauer, S.; Ellwood, Simon; Wise, R.; Yaeno, T.; Maekawa, T.; Schulze-Lefert, P. (National Academy of Sciences, 2016)
© 2016, National Academy of Sciences. All rights reserved. Disease-resistance genes encoding intracellular nucleotide-binding domain and leucine-rich repeat proteins (NLRs) are key components of the plant innate immune system and typically detect the presence of isolate-specific avirulence (AVR) effectors from pathogens. NLR genes define the fastest-evolving gene family of flowering plants and are often arranged in gene clusters containing multiple paralogs, contributing to copy number and allele-specific NLR variation within a host species. Barley mildew resistance locus a (Mla) has been subject to extensive functional diversification, resulting in allelic resistance specificities each recognizing a cognate, but largely unidentified, AVRa gene of the powdery mildew fungus, Blumeria graminis f. sp. hordei (Bgh). We applied a transcriptome-wide association study among 17 Bgh isolates containing different AVRa genes and identified AVRa1 and AVRa13, encoding candidate-secreted effectors recognized by Mla1 and Mla13 alleles, respectively. Transient expression of the effector genes in barley leaves or protoplasts was sufficient to trigger Mla1 or Mla13 allele-specific cell death, a hallmark of NLR receptor-mediated immunity. AVRa1 and AVRa13 are phylogenetically unrelated, demonstrating that certain allelic MLA receptors evolved to recognize sequence-unrelated effectors. They are ancient effectors because corresponding loci are present in wheat powdery mildew. AVRA1 recognition by barley MLA1 is retained in transgenic Arabidopsis, indicating that AVRA1 directly binds MLA1 or that its recognition involves an evolutionarily conserved host target of AVRA1. Furthermore, analysis of transcriptome-wide sequence variation among the Bgh isolates provides evidence for Bgh population structure that is partially linked to geographic isolation.